Regulation of glucose metabolism in oral streptococci through independent pathways of glucose 6-phosphate and glucose 1-phosphate formation. - Keevil, C W (1984)
In vivo rates of glucose uptake and acid production by oral streptococci grown in glucose- or nitrogen-limited continuous culture and batch culture were compared with the glucose phosphorylation activities of harvested, decryptified cells. The strains examined contained significant phosphoenolpyruvate-phosphotransferase system (PTS) activity, measured by a glucose 6-phosphate (G6P) dehydrogenase-linked assay procedure, but this activity was insufficient to account for the in vivo glucose uptake rates. However, ATP was a superior phosphoryl donor to phosphoenolpyruvate, and unlike the PTS, phosphoryl transfer with ATP was insensitive to bacteriostatic concentrations of chlorhexidine, suggesting glucokinase-mediated G6P formation. Again, G6P formation from the PTS and glucokinase reactions was not commensurate with some of the glucose uptake rates observed, implying that other phosphorylation reactions must be occurring. Two novel reactions involving carbamyl phosphate and acetyl phosphate were identified in some of the strains. No G6P formation was detected with these potential phosphoryl donors, but in the presence of phosphoglucomutase, glucose 1-phosphate (G1P) formation was evident, which was insensitive to chlorhexidine. G1P is a precursor of glycogen, and good correlation was obtained between G1P formation activity and endogenous metabolism of washed cells measured either as a rate of acid production at a constant pH 7 or as a decrease in pH with time in the absence of titrant. A "league table" of abilities to synthesize G1P and produce acid from endogenous metabolism was compiled for oral streptococci grown in batch culture. This indicated that Streptococcus mutans Ingbritt and Streptococcus sanguis Challis were unable to form G1P or produce much acid endogenously, whereas increasing activities were obtained with Streptococcus salivarius, Streptococcus sanguis, and Streptococcus mitis. In particular, S. mitis had the highest G1P formation activities and was able to decrease the pH to less than 5 in 15 min by endogenous metabolism alone. The data are consistent with the intracellular accumulation of free glucose driven by proton motive force when PTS activities are low and the subsequent phosphorylation to either G6P for metabolism via glycolysis or G1P for glycogen biosynthesis. The accumulation of acetyl phosphate during glucose-limited growth and the availability of arginine for catabolism to carbamyl phosphate provide an explanation as to why some glucose-limited oral streptococci continue to synthesize glycogen under these conditions, which might prevail in plaque.